Pygmalion Effect: Esensi Ekspektasi Positif terhadap Keberhasilan - Maria Jenah; Ivana Destya Treeocta Fernandez; Novia Sumarni; Masduki Asbari; Salsabilla Agusna; Novi Ramayanti (Literaksi: Jurnal Manajemen Pendidikan, 2023)
This study aims to determine the impact of the Pygmalion effect and its application in everyday life. This research is qualitative with a descriptive approach which is carried out using the note-taking method. The data source for this research is a video on the YouTube channel (Berilmu, 2022) entitled "Pygmalion Effect, The Power of Trust." The Pygmalion effect is defined as a psychological phenomenon in which positive expectations can generate self-confidence and motivation that can affect one's achievement. The opposite of the Pygmalion effect is the golem effect. The golem effect is a psychological phenomenon where negative expectations lead to demotivation resulting in poor performance. The conclusion of this study is that the proper application of the Pygmalion effect will have a good impact.